Goal attainment scaling outcomes in general inpatient rehabilitation: association with functional independence and perceived goal importance and difficulty - Irina Churilov; Kim Brock; James M. Churilov; Emma Sutton; David Murphy; Richard J. MacIsaac; Elif I. Ekinci (Medical Journals Sweden, 2020)
Objective: To investigate the association of goal attainment scaling outcomes with change in the Func-tional Independence Measure, and the association between the perceived importance, difficulty and degree of achievement of individual goals in general inpatient rehabilitation. Design: Prospective cohort study. Participants: A total of 208 participants admitted to inpatient rehabilitation in a metropolitan tertiary referral hospital in Melbourne, Australia. Methods: Participants determined the nature of the goals and their importance, and therapists determined the difficulty of the goals. The associations were investigated using median regression and random effect ordinal regression. Results: An increase of each point in the goal attainment scaling score was associated with an adjusted median increase of 0.34 points (95% confidence interval (CI): 0.18-0.5, p < 0.001) in Functional Independence Measure change. More important goals of similar difficulty (very important vs a little important: adjusted common odds ratio (cOR) = 1.97, 95% CI: 1.01-3.83, p = 0.045) and less difficult goals of similar importance (moderately difficult vs a little difficult cOR = 0.59, 95% CI: 0.04-0.87, p = 0.007; very difficult vs a little difficult cOR = 0.59, 95% CI 0.37-0.94, p = 0.027) were better achieved. Conclusion: Rehabilitation progress measured using the goal attainment scaling method is associated with changes in functional outcomes. For goals with similar difficulty, those with higher importance were better achieved, while for goals with similar importance, less difficult goals were better achieved.